Nordic film cultures and cinemas of elsewhere - Stenport, Anna Westerståhl; Lunde, Arne Olav (Traditions in world cinema., 2019)
Nordic Film Cultures and Cinemas of Elsewhere introduces a new concept to Nordic film studies as well as to other small national, transnational and world cinema traditions.